Effect of extrusion ratio on microstructure and mechanical properties of Mg−2.5Sn−1.5Zn−0.8Ca−0.1Y alloy. (5th April 2019) - Junfeng, Zhang; Lin, Deng
Abstract: To examine the influence of extrusion ratio on microstructure and mechanical properties, a new as-extruded Mg−2.5Sn−1.5Zn−0.8Ca-0.1Y (mass fraction, %) alloy was invented and tested. Results show that incomplete dynamic recrystallization (DRX) appeared during hot extrusion ; the number of un-DRXed grains and the average size of DRXed grains became smaller with the extruding ratio rising from 5 to 10, and the basal texture became worse, together with coarse MgSnCa phase being crushed into particles and fine Mg2 Sn phase precipitated from α -Mg matrix. The yield strength, tensile strength and elongation ratio under extruding ratio10 were 218.4 MPa, 288.6 MPa and 18.61% respectively, which have increased by 36.0%, 17.7% and 13.5% correspondingly by contrast with that of under extruding ratio 5.